Regulatory considerations in the design, development and quality of monoclonal antibodies and related products for the diagnosis and treatment of cancer - Shapiro, Marjorie A. (Frontiers in Oncology, 2024)
Over 160 therapeutic and in vivo diagnostic monoclonal antibodies have been approved by the US FDA since the first monoclonal antibody, muromonab, was approved in 1986. Approximately 42% of these approvals were for the treatment or in vivo diagnosis of oncology indications, although some products are no longer marketed. This review will look at the history of monoclonal antibody development and approvals, discuss current antibody-based modalities, regulatory considerations for engineering approaches, critical quality attributes for different modalities, immunogenicity of mAbs across oncology products, and the future directions for development of therapeutic and diagnostic monoclonal antibody-based products.